Evaluating Social Media Marketing Performance in Five-Star Hotels: A Managerial Perspective from Turkey - GÜRBÜZ, Esen; ORMANKIRAN, Gizem Aslıhan (International Journal of Contemporary Economics and Administrative Sciences, 2025)
This study aims to determine the impact of five-star hotel managers’ evaluation of the importance and effectiveness of using social media for marketing on their subsequent monitoring of social media (SM) analytics. Furthermore, it seeks to investigate the effect of such monitoring on the evaluation of Social Media Marketing Performance (SMMPE). The findings indicate that five-star hotel managers’ perception of social media (SM) as an essential marketing tool positively influences their attention to metrics known as SM Analytics. However, their evaluation of Social Media Marketing (SMM) in terms of consumer engagement and effectiveness does not significantly influence their tendency to monitor SM Analytics. It was observed that managers’supervision of SM Analytics impacts the SMMPE across various dimensions: at the consumer level, assessed through marketing metrics like consumer attitudes and behaviors; at the firm’s financial level, via output/input ratios and financial indicators; and at the market level, through the evaluation of competitor performance. The research results highlights the nuanced relationship between managerial perceptions, analytics engagement, and performance evaluation in the context of social media marketing within the luxury hotel sector